Research on the Value Added Effect of Venture Capital Supporting the Development of Venture Enterprise - MENG, QINGCAI (Pacific International Journal, 2024)
The key to national innovation driven development is to leverage the supportive role of venture capital in the development of venture enterprises. This paper takes companies listed on the New Third Board from 2016 to 2021 as samples and uses a multiple linear regression model to study the impact of venture capital on the development of venture enterprises. It further explores the value-added effect of the impact from the probability dimension of being selected into the innovation layer.Research has found that venture capital entering the New Third Board has a higher probability of being selected for the innovation layer, and exerts a positive value-added effect; The impact of venture capital on listed companies on the New Third Board is mainly reflected in the strong screening ability of venture capital, which can screen high-quality risk enterprises, and increase the probability of listed companies being selected for the innovation layer through the value-added mechanism of venture capital. The research not only reveals the impact and value-added effect of venture capital on the development of venture enterprises, but also provides empirical evidence for the country to improve its financial service system and use the capital market to promote national innovation driven development.